The Impact of Brand Awareness, Brand Identity, and Brand Image on Lovemarks and Brand Evangelism: A Comparative Analysis of Smartphone Users - Sukhabot, Sasiwemon; Phetburi, Wanwisa (Journal of Cultural Analysis and Social Change, 2025)
The study examines the motivations for brand evangelism in the smartphone sector, along with the determinants of brand love and respect. It also analyzes and compares businesses utilizing diverse marketing strategies to ascertain if the influence metrics and frameworks vary. The study included 800 Thai consumers aged 18 and above who used the two predominant smartphone manufacturers with the biggest market share in 2024. They have utilized these gadgets for over six months. Brand awareness, brand identity, and brand image were evaluated. The data were analyzed using structural equation modeling techniques and multiple group analysis. The findings indicated that brand identity and brand image significantly affect brand love and respect, which subsequently promote brand evangelism. Brand awareness directly influenced brand respect, although it did not affect brand love. The brand, despite its extensive awareness, failed to establish a deep emotional connection with individuals. The study provides theoretical insights on Lovemarks and brand evangelism, particularly inside firms that give emotional, social, and functional value. Furthermore, despite the deployment of diverse marketing strategies by these businesses, the research reveals no distinction between the underlying characteristics of brand love and respect and their impact on brand evangelism within the smartphone industry, even across multiple contexts. By employing this strategy, companies may adapt marketing strategies and evaluate brand advocacy across several Asian countries and many industries.